2013
DOI: 10.1136/bmjopen-2013-002910
|View full text |Cite
|
Sign up to set email alerts
|

A population-based cross-sectional study of the association between facial morphology and cardiometabolic risk factors in adolescence

Abstract: ObjectiveTo determine whether facial morphology is associated with fasting insulin, glucose and lipids independent of body mass index (BMI) in adolescents.DesignPopulation-based cross-sectional study.SettingAvon Longitudinal Study of Parents and Children (ALSPAC), South West of England.ParticipantsFrom the ALSPAC database of 4747 three-dimensional facial laser scans, collected during a follow-up clinic at the age of 15, 2348 white British adolescents (1127 males and 1221 females) were selected on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…In [30] Ferrario et al observed an increase in some facial dimensions in a study on the face morphology of obese adolescents. Djordjevic et al in [31] reported an analysis of facial morphology of a large population of adolescents under the influence of confounding variables: though the statistical univariate analysis showed that four principal face components (face height, asymmetry of the nasal tip and columella basis, asymmetry of the nasal bridge, depth of the upper eyelids) correlated with insulin levels, the regression coefficients were weak, and no significance persisted in the multivariate analysis.…”
Section: Digital Anthropometric Measurementsmentioning
confidence: 99%
“…In [30] Ferrario et al observed an increase in some facial dimensions in a study on the face morphology of obese adolescents. Djordjevic et al in [31] reported an analysis of facial morphology of a large population of adolescents under the influence of confounding variables: though the statistical univariate analysis showed that four principal face components (face height, asymmetry of the nasal tip and columella basis, asymmetry of the nasal bridge, depth of the upper eyelids) correlated with insulin levels, the regression coefficients were weak, and no significance persisted in the multivariate analysis.…”
Section: Digital Anthropometric Measurementsmentioning
confidence: 99%
“…Indeed, quantitative soft-tissue facial data in the three dimensions can currently be obtained by digital, computerized anthropometry [10][11][12][13][14][15][16][17][18][19][20][21]. Current technology allows fast and non-invasive optical scans of facial surface, providing a global assessment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In children and adolescents previous studies reported bimaxillary prognathism and relatively greater horizontal and anteroposterior facial measurements in obese subjects compared to normalweighted peers [23][24][25][26]. Nevertheless, no evidence that facial morphology is importantly related to cardiometabolic outcomes was found in a large cohort of adolescents [17]. Studies on obese adults mostly focused on patients with obstructive sleep apnea (OSA) [26], while investigations on the relationships among obesity, facial morphometry and MS have not been conducted so far.…”
Section: Introductionmentioning
confidence: 99%
“…Much research into the "science of a smile" also focuses on the effects of aging and biological sex on the shape and appearance [4][5] and also the dynamics [6][7][8] of smiling. Recent investigations have been greatly enhanced by the use of three-dimensional (3D) imaging techniques [9][10][11][12][13] that allow both static and dynamic imaging of the face. Clinically, this research has led to improved understanding of orthognathic surgery [9], malocclusion [10], associations between facial morphology and cardiometabolic risk [11], lip shape during speech [12], facial asymmetry [13], and sleep apnea [14] (to name but a few examples).…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have been greatly enhanced by the use of three-dimensional (3D) imaging techniques [9][10][11][12][13] that allow both static and dynamic imaging of the face. Clinically, this research has led to improved understanding of orthognathic surgery [9], malocclusion [10], associations between facial morphology and cardiometabolic risk [11], lip shape during speech [12], facial asymmetry [13], and sleep apnea [14] (to name but a few examples). Clearly also, facial simulation is of much interest for human-computer interfaces (see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%